Imaging characterization of pseudomyxoma peritonei: a case report - Araceli Cue-Castro; Oscar Villagomez-Figueroa (Journal of the Mexican Federation of Radiology and Imaging)
Pseudomyxoma peritonei (PMP) is a rare condition characterized by the accumulation of mucinous (gelatinous) fluid in the abdominal cavity. This case report describes an 86-year-old woman with nonspecific abdominal symptoms and a progressive increase in her abdominal circumference. Abdominal ultrasound (US) showed a complex soft tissue mass attached to the liver and the visceral side of the peritoneum on the anterior wall. We observed an “onion skin” sign”–characterized by alternating layers of dense and less dense tissue–, and a “starburst” appearance–characterized by radial echoes extending from a central point. Abdominal contrast computed tomography (CCT) showed visceral scalloping and “omental caking,” due to extensive peritoneal involvement–the omentum appeared diffusely thickened and adhered with centralized bowel loops. We identified an ill-defined mass in the cecum. Cytochemical analysis of the peritoneal fluid revealed a mucinous material with scant epithelial cellularity. PMP was diagnosed based on the classic imaging findings on abdominal US and CCT. This case report is intended for educational purposes. By documenting this case, we seek to improve the understanding of this rare neoplastic condition, emphasizing its imaging features on US and CCT.